บทบาทเชิงวารสารศาสตร์แบบก่อกระแสของผู้จัดการออนไลน์ในช่วงวิกฤตการณ์ทางการเมืองไทย พ.ศ. 2549 - พรรณอุษา ธีรภาพภัทรกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
This study is a qualitative and quantitative research. The research aimed at studying the advocacy journalism role of Manager Online website during the 2006 political crisis, the factors influenced on this role, and the conflict on code of ethics upon content producers of this website. The study relies on the following research methodologies : content analysis on 5 categories of content including headlines, political news, articles, analyses cartoons. The timeframe for content analysis is 4 periods during 23rd January – 19th October 2006. Furthermore, in-depth interviews were carried out with editors, content producers of Manager Online, media professionals, communication scholars and media activists . This research has these findings: 1. Manager Online clearly plays the advocacy journalism role during the 2006 political crisis by opposing the Thaksin Shinawatra administration; 2. 93.60% of content from the sampled units of analysis in Manager Online was found to be against the Thaksin Shinawatra administration; 3. The styles of language appeared on Manager Online are irony, creating new words, contrasts, and metaphor; 4. The producers of Manager Online apply these framing techniques – theme selection, figures of speech, stories (myths and legends), slogans, photos, use of news sources, presentation, problem definition, and moral evaluation; 5. Most of the news sources used by Manager Online were against the Thaksin Shinawatra administration; 6. The factors that influenced on the advocacy journalism role of Manager Online during the 2006 political crisis are technology, organization ownership and political crisis; 7. The content producers of Manager Online have no conflict on code of ethics because they think they are protecting the public interest.